Isospin Effects on Subthreshold Particle Production - Gaitanos, T.; Ferini, G.; Colonna, M.; Di Toro, M.; Wolter, H. H. (HNPS Advances in Nuclear Physics, 2019)
The production/absorption rate of particles in compressed and heated asymmetric matter is studied using a Relativistic Mean Field (RMF) transport model with an isospin dependent collision term. We show that the K+/K° ratio reflects the isospin effects on the production rates just because of the large sensitivity around the threshold. The results are very promising with respect to the possibility of a direct link between particle production data in exotic Heavy Ion Collisions (HIC) and the isospin dependent part of the Equation of State (EoS) at high baryon densities.